Causes and Coping with Visual Impairment and Blindness - Rumelt, Shimon (IntechOpen, 2018)
About 4% of the world population has visual impairment or blindness. This book is aimed at addressing different causes of visual impairment and blindness, their epidemiology, manifestations, risk factors, prevention of progression, and treatment. It is aimed at encouraging physicians and researchers to increase efforts to prevent irreversible and treat reversible blindness for the betterment of the world. Therefore, it is essential to be fully aware and knowledgeable of the manifestations of the diseases causing blindness, and this book covers some of their different aspects. Each chapter was written by experts from around the globe. Thus, it reflects the importance of the subject.